1968
DOI: 10.1051/animres:19680104
|View full text |Cite
|
Sign up to set email alerts
|

Résultats Obtenus Au Cours De l'ÉTUDE De Quelques Facteurs Importants De l'INSÉMINATION Artificielle Ovine

Abstract: École nationale supérieure agronomique, Centre de Recherches agronomiques du Midi, 31-M ontpellier Institut national de la Recherche agvonomique SOMMAIRE La recherche d'une technique d'insémination artificielle dans l'espèce ovine a été orientée vers l'étude du milieu de dilution, de la durée et de la température de conservation du sperme et du nombre quotidien d'interventions. Au cours de nos expériences, 1 59 8 brebis de races Lacaune et Ile-de-France ont été utilisées. W Une comparaison entre le lait de vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…More recently, Mara et al (2005) found an improvement in fertility and blastocyst rate development in an in vitro experiment, when sperm were stored at 15 • C in presence of the antioxidant TEMPOL, and Casao et al (2010) reported an increase in the cleavage rate after treating sperm with small amounts of melatonin. In addition to the effects of antioxidants, there was an overall greater quality in the samples of the present study that were maintained at 15 • C. Although there are many reports on the quality of ram semen stored either at 15 or 5 • C (Salamon and Maxwell, 2000), only a few of these previous studies directly compared both temperatures under similar conditions (Colas et al, 1968;Hollinshead et al, 2004;O'Hara et al, 2010). These direct-comparison studies are necessary to fully understand differences between these two temperatures while controlling for confounding variables, and thus this was one of the objectives of the present study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…More recently, Mara et al (2005) found an improvement in fertility and blastocyst rate development in an in vitro experiment, when sperm were stored at 15 • C in presence of the antioxidant TEMPOL, and Casao et al (2010) reported an increase in the cleavage rate after treating sperm with small amounts of melatonin. In addition to the effects of antioxidants, there was an overall greater quality in the samples of the present study that were maintained at 15 • C. Although there are many reports on the quality of ram semen stored either at 15 or 5 • C (Salamon and Maxwell, 2000), only a few of these previous studies directly compared both temperatures under similar conditions (Colas et al, 1968;Hollinshead et al, 2004;O'Hara et al, 2010). These direct-comparison studies are necessary to fully understand differences between these two temperatures while controlling for confounding variables, and thus this was one of the objectives of the present study.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, in previous studies when INRA96 was used, as was the case in the present study, the differences in sperm quality for the different temperatures were much less at 48 h of storage. Colas et al (1968) also detected small differences when comparing sperm quality after 2 and 14 h (milk-catalase extender) of storage, whereas Hollinshead et al (2004) stored the samples up to 24 hand found no differences.…”
Section: Discussionmentioning
confidence: 90%
“…Ejaculated spermatozoa were diluted into skimmed milk and brought to 15 °C (Colas et al, 1968). Epididymal spermatozoa were obtained from different segments of the epididymidis caput (distal), corpus (I = middle, 11 = inferior middle and III = distal part), and cauda (proximal and distal) according to Fournier-Delpech et al (1977).…”
Section: Methodsmentioning
confidence: 99%
“…J. Anim. Sci.59: 685-691 (Dec. 1979) (Ortavant 1977;Robinson 1965Robinson , ,1967 concentration of 900 x 106/ml, using a skim milk-citrate diluent at 30"C (Colas et al 1968). The diluted semen was cooled slowly and maintained at 16"C for up to 12 h.…”
mentioning
confidence: 99%